THE ELECTRICAL TRANSFORMER –AN INVENTION THAT REVOLUTIONIZED ELECTRICAL ENGINEERING (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
The transformer is the equipment that revolutionized the long-distance transmission of electrical energy. Many of the applications of electricity are related to this electrical equipment, which has been designed and perfected through the contributions of numerous experimenters, scientists, engineers, and technicians over two hundred years of creative efforts. This work synthesizes the stages of accumulation of scientific and technical knowledge in electromagnetism, which led to the patenting and construction of the first electrical transformer in 1884-1885. In addition to the chronological milestones of the genesis of the electrical transformer, the contributions made by this equipment to the inauguration of a new stage in the development of human society based on comfort and productivity are also illustrated. The new directions of research and development in which sustainability is the key element show that the electrical transformer will not remain just an artifact preserved in museums.DOI: https://doi.org/10.36801/apme.2024.1.3
Keywords: Transformer